Aerodynamic optimization of pylons to improve rear wing performance using passive and active systems - Upadhyaya, Avaneesh; Nagaraja Rao, Kaushik (My University, 2021)
In collaboration with Automobili Lamborghini S.p.A, an aerodynamic investigation was carried out on a dual pylon rear wing assembly to improve cornering stability of a car at high speeds. The pylon's primary purpose is to provide structural support to the wing. However, this project aimed at improving the performance of Aventador SV's rear wing using aerodynamically optimized pylons that not only boosted its downforce generating capabilities, but also generated large side forces at higher yaw angles. The project goals were fulfilled in two phases. The first phase involved development of pylon airfoils that would keep the flow attached within a range of ±15 yaw angles, without augmenting the drag when compared to NACA0010. A surrogate based model was used to generate these airfoils. 2D simulations were performed on the airfoils along with passive and active systems to achieve attached flow around the pylons, thus, generating more downforce by improving suction under the wing. Single slot approach was used to create passive slots that improved flow on one side of the design at the expense of the other. The active flow control was implemented in two ways, blowing and suction. Throughout this study, active blowing has held precedence due to energy constraints. Three airfoils with better performance than NACA0010 at higher yaw angles were selected for next phase. In the second phase, airfoils from 2D study were used to carry out 3D simulations using RANS solver on several wing and pylon combinations, without a car body, in a quest to find the optimum performing pylon. A study was conducted to analyse the effect of different pylon positions, sizes, and profiles along with passive and active systems on the air flow around the wing. With the profiles generated in 2D study, an improvement in the performance of the wing was achieved at higher yaw angles. Wherever the flow detached over the pylon, passive and active systems showed signs of improvement.
Keywords: Pylons; Rear Wing; Aerodynamics; Asymmetric Airfoil; Low Reynolds; Lift; Drag; CFD; Passive; Active; STAR-CCM+